The world of rules : a somewhat different measurement of the world - Schuppert, Gunnar Folke (Global perspectives on legal history, 2017)
"This book takes a stand against the narrowing focus of (German) jurisprudence on state law, rooted in the history of the territorially organised nation state. In the shadow of this tradition, state( -hood) law was only conceived of as state law. However, a gradual decoupling of state and law is observable - not least because of globalisation - which inevitably entails a pluralisation of legal regulations. Jurisprudence has to react to this, if it wants to remain relevant. This can happen through a broadening of its horizon towards a more far-reaching "science of regulation", in order to grasp the increasing "Variety of Rules" adequately. State law remains an important and central type of law, yet it is no longer the sole type. If that is the case, it becomes necessary to analyse the following three spheres: (1) the plurality of normative orders, especially those of non-state character; (2) the plurality of norm producers, from state legislature to transnational networks of regulation; (3) finally, the plurality of norm enforcement regimes, from states' judiciaries via the judiciary of (international) sport to the exercise of social pressure (e. g. political correctness). Those findings of plurality inevitably lead to the follow-up problem of a redefinition of the concept of law and to the question, which types of law/norms can be identified meaningfully."